Generalised joint hypermobility and shoulder joint hypermobility, – risk of upper body musculoskeletal symptoms and reduced quality of life in the general population - Birgit Juul-Kristensen (BMC Musculoskeletal Disorders, 2017)
Abstract Background Generalised Joint Hypermobility (GJH) is a hereditary condition with an ability to exceed the joints beyond the normal range. The prevalence of GJH in the adult population and its impact on upper body musculoskeletal health and quality of life has mostly been studied in selected populations. The aims of this study were therefore, firstly to study the prevalence of GJH and GJH including shoulder hypermobility (GJHS), in the general Danish adult population; secondly to test the associations between GJH or GJHS and upper body musculoskeletal symptoms and health-related quality of life (HRQoL). Methods The study was cross-sectional where 2072 participants, aged 25–65, randomly extracted from the Danish Civil Registration System), were invited to answer a questionnaire battery (Five-Part Questionnaire for classification of GJH, Standardised Nordic Questionnaire for musculoskeletal symptoms, EuroQoL-5D for HRQoL). Results Totally 1006 (49%) participants responded. The prevalence of GJH and GJHS were 30% (n = 300) and 5% (n = 51), respectively. Compared with Non GJH (NGJH), participants with GJH and GJHS had Odds Ratio (OR) of 1.5-3.5 for upper body musculoskeletal symptoms within the last 12 months (mostly shoulders and hands/wrists). GJH and GJHS also had OR 1.6–4.4 for being prevented from usual activities, mostly due to shoulder and neck symptoms. Furthermore, GJH and GJHS had OR 2.2–3.1 for upper body musculoskeletal symptoms lasting for more than 90 days (neck, shoulders, hand/wrists), and 1.5–3.5 for reduced HRQoL (all dimensions, but anxiety/depression) compared with NGJH. Generally, most OR for GJHS were about twice as high as for those having GJH alone. Conclusions GJH and GJHS are frequently self-reported musculoskeletal conditions in the Danish adult population. Compared with NGJH, GJH and especially GJHS, present with higher OR for upper body musculoskeletal symptoms, more severe symptoms and decreased HRQoL.